Oil based inactivated vaccine formulation for furunculosis (A. salmonicida) and protective immune response of rainbow trout and brown trout - Akram, Muhammad; Hafeez-Ur-Rehman, Muhammad; Abbas, Farzana; Altaf, Imran; Kanwal, Sidra; Ali, Kashif; Gulzar, Nabila; Ajmal, Muhammad; Asad, Muhammad; Iqbal, Javaid (Penerbit Universiti Kebangsaan Malaysia, 2023)
The development and growth of the fisheries and aquaculture industries are significantly hampered by illnesses. It is critical to combat pathogenic illnesses, especially bacterial ones. Furunculosis in salmon is mostly brought on by Aeromonas salmonicida in rainbow and brown trout. To control this pathogen, vaccines have been identified as a significant tool. In the present study, we have formulated an inactivated vaccine with oil as an adjuvant and estimated its efficacy. The lethal dose of ArS-Pak-19, was calculated and injected intraperitoneally to the fishes. To analyze the infection, samples of kidney, liver, spleen, and blood were collected at specific times. To estimate the immunogenicity of the vaccine, an experiment was designed. One hundred sixty fishes were distributed into 8 tanks including, six experimental groups and two control groups with its replicates, vaccines injected intraperitoneally 1.6 × 107 , 1.6 × 108 , and 1.6 × 109 and blood samples were taken fortnightly for 56 days to calculate the antibodies titers. After immunization these groups were challenged with Aeromonas salmonicida (ArS-Pak-19) intraperitoneally. At 7th day of post infection, it appeared in the liver, spleen, and kidney. The relative percentage of survival was estimated with control groups at 30 days after challenge. The relative percentage of survival was 80%. The IgM titers were higher at 24 days of post immunization. We also analyzed that antibodies non-specifically bound with the A-layer of Aeromonas salmonicida. The findings of this study offer evidence that vaccinations boost fishes immunity and serve as a roadmap to further vaccination initiatives.